Improving Solar Cell Efficiency PV/T Using NEPCM by FEM Method - Adriana, Syarifah; Jelita, Marhama (Jurusan Teknik Elektro Universitas Andalas, 2025)
Energy generated from photovoltaic (PV) systems is often wasted, with about 80% converted to heat and only 20% converted to electricity. This indicates the need for further research to improve the energy conversion efficiency in PV systems. This study aims to analyze the cell efficiency and power generation in a photovoltaic-thermal (PVT) system with variations in nano-encapsulated phase change material (NEPCM) concentration and reservoir thickness. The developed PVT configuration includes a photovoltaic cell layer, a thermal paste layer, a reservoir wall, and a channel filled with nanofluid containing NEPCM surrounded by a protective shell. The research method involves simulation using the Finite Element Method to measure system performance regarding energy conversion efficiency, with encapsulated PCM concentration variations at 2%, 10%, and 20%. Additionally, the laminar flow velocity used is 0.5 m/s under steady-state conditions, and the thickness of the PCM material used is 1 mm and 15 mm. The results show that increasing the NEPCM concentration by 5% can improve the electrical and thermal performance of the system by more than 50%. In addition, variations in reservoir thickness also contribute to the overall efficiency. This study concludes that the proposed PVT configuration can improve energy efficiency and optimize thermal management in the system, making it an effective solution for developing renewable energy technologies. Thus, implementing NEPCM in PVT systems can significantly contribute to overall energy efficiency.